2010
DOI: 10.1016/j.mce.2009.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis and development of adipose tissue

Abstract: Obesity is a common disorder and related diseases, such as diabetes, atherosclerosis, hypertension, cardiovascular disease and cancer, are a major cause of mortality and morbidity in Western-type societies. Development of obesity is associated with substantial modulation of adipose tissue structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
165
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(171 citation statements)
references
References 98 publications
6
165
0
Order By: Relevance
“…The expression of many angiogenesis regulatory factors changes during adipogenesis. 32 TSP-1 is consistently found in the adipose tissue secretome. [33][34][35] TSP-1 levels are modulated during the differentiation of preadipocyte into adipocytes.…”
Section: Discussionmentioning
confidence: 93%
“…The expression of many angiogenesis regulatory factors changes during adipogenesis. 32 TSP-1 is consistently found in the adipose tissue secretome. [33][34][35] TSP-1 levels are modulated during the differentiation of preadipocyte into adipocytes.…”
Section: Discussionmentioning
confidence: 93%
“…port the enlarged and expanded adipocyte pool, an appropriate stromovascular network must form in parallel (3)(4)(5). It is possible that expansion of the vascular network may actually precede adipocyte growth, as is known to occur during embryonic development, when the formation of the adipose tissue vascular network precedes the emergence of adipocytes (6).…”
mentioning
confidence: 99%
“…Hypoxia has recently been proposed as a possible initiator instigating macrophage infiltration and inflammation in obese WAT (5)(6)(7). The expansion of WAT is critically dependent on the microvasculature and angiogenesis in this tissue (8,9). It has been suggested that the enlargement of adipocyte size in obesity exceeds the normal oxygen diffusion distance and compromises the effective oxygen supply from the vasculature, leading to localized hypoxia (10).…”
mentioning
confidence: 99%